GERAKAN PEMULUNG SAMPAH SEBAGAI KEPEDULIAN LINGKUNGAN DAN TABUNGAN EMAS BERSAMA SRIKANDI MASYARAKAT KOTA JAMBI - Suprihatin, Suprihatin; Tamsir, Tamsir; Kusnadi, Edy (Nindikayla Institute, 2023)
In the framework of National Waste Care Day (HPSN), which is celebrated every February 21. Jambi people take part in protecting the surrounding environment. The problem of waste in Indonesia must be a major concern involving synergy and concern from all components of society in its management. Participate actively in helping waste management in the form of waste segregation activities. The results of sorting are then submitted to the waste bank or waste collection site. Being able to sort out organic waste and inorganic waste wisely, we can get lots of benefits. Providing knowledge, insight and inspiration in managing household waste so that Indonesian women realize their important role as environmental managers from the smallest unit, namely their household and the immediate environment. This can have a real positive impact on the earth and is a step in making the earth healthy